Site-specific survival rates for cancer of unknown primary according to location of metastases - Hemminki, Kari (Epidemiology, 2013)
Cancer of unknown primary (CUP) is diagnosed at the metastatic stage and despite extensive diagnostic work-up the primary tumor often remains unidentified. Limited population-based survival data are available for metastatic location and none are available that link the location with the cause of death, which might give clues about the tissue-of-origin. A total of 9,306 CUP patients with extranodal metastases of adenocarcinoma and undifferentiated histology were identified from the Swedish Cancer Registry. Hazard ratios (HRs), mean survival times and Kaplan-Meier survival curves were provided according to CUP location at diagnosis and cause of death. The median survival was shortest (2 months) for patients with liver and longest (5 months) for those with nervous system metastases. Lung cancer was the most common cause of death in patients with CUP metastasis in the respiratory system, nervous system, bone and skin, with a median survival of 3 months. Patients with peritoneal/retroperitoneal and pelvical metastasis died not only of ovarian cancer, with a favorable median survival of 8 months, but also of pancreatic and colorectal cancers. Patients with pancreatic, liver, biliary and colorectal cancers with liver metastasis succumbed quickly. The data show that the location of metastases predicts site-specific cancer deaths which in turn may point to the hidden primary tumor. The results should facilitate the management of CUP in proposing that the diagnostic arsenal should target the lungs when metastases are diagnosed in the respiratory or nervous system, bone or skin; ovarian tumors should be suspected after diagnosis of pelvical metastases.